Synthesis, characterization, and enhanced electrochemical behavior of polypyrrole doped ZrO2–ZnO electrode materials for supercapacitor applications - Zenasni, Mounya; Belhadj, Hafida; Kiari, Mohamed; Alelyani, Magbool; Alhailiy, Ali B.; Benyoucef, Abdelghani; Bakkour, Youssef (Frontiers in Energy Research, 2023)
electrodes were synthesized using an in-situ chemical oxidative method. The samples were characterized by XRD, FTIR, XPS, UV-vis, TGA and BET. In addition, the electrochemical characteristics of the electrodes is tested by cyclic voltammetry (CV), galvanostatic charge&discharge (G.C.D) and electrochemical impedance spectroscopy (E.I.S). The values of the specific capacitances and the energy densities of the PPy@ZrO2-ZnO (1.0) PPy@ZrO2-ZnO (0.5) at a current density of 0.5 A•g −1 are recorded as (395.3 F•g −1 and 508.5 Wh•kg −1 ) and (195.3 F•g −1 and 351.5 Wh•kg −1 ), respectively. Furthermore, the electrode stability for the formed samples was also determined, which exhibited specific capacitance retention at 90.